Trivelpise-Gould modes of waveguide partially filled with neutral or non-neutral plasma - Yeliseyev, Yu.N. (Problems of Atomic Science and Technology, 2022)
The frequency spectra of eigenmodes with azimuthal number m = 1 are determined by numerical methods for a waveguide partially filled with neutral or non-neutral plasma. Calculations are performed within the entire permissible range of electron density or magnetic field strengths, for different values of the degree of charge neutralization and the longitudinal wave vector. Areas of existence of bulk and surface electronic modes of waveguide are also defined. The results are presented in the form of dependences on the parameter q = 2ωₚₑ²/ωcₑ².